APPLICATION OF SMART ENVIRONMENT WITH FUZZY LOGIC METHOD BASED ON INTERNET OF THINGS - Mhd Furqan; Rakhmat Kurniawan R; Ahmad Fauzi (INFOKUM, 2020)
In Indonesia, air pollution is a very concern, many risks are resulting from air pollution, including the risk of blood cancer. But many people are not aware of this as a result, many are affected by respiratory infections, asthma, and lung cancer due to air pollution. Along with technological developments, a new concept emerged, namely the Internet of things, from the development of the Internet of Things, which resulted in many discoveries, one of which was the Smart Environment. With Smart Environment we can monitor the quality level of an environment, one of which is air quality. The amount of information related to air pollution is the reason for the author to make a tool that uses the Nodemcu microcontroller-based MQ7 sensor which is expected to help reduce the risk generated from air pollution, especially carbon monoxide (CO). This tool also applies the concept of the internet of things so that the results of sensor readings can be monitored online from anywhere and anytime in realtime. There is a classification of air pollution levels in this tool including healthy air, unhealthy air, and dangerous air, healthy air is in the value range 0-100 PPM, unhealthy air is in the value range of 100-200 PPM, and dangerous air is in the value range> 200 PPM. Fuzzy logic was chosen as the method in this research because this method is suitable for most real-time problems such as making decisions to determine the level of air pollution that is uncertain and changing. The results of the MQ7 sensor detection of carbon monoxide are monitored through the Indonesian-made Internet of Things platform, Antares.id.